S28 Liraglutide 3.0 Mg Reduces Severity Of Obstructive Sleep Apnoea And Body Weight In Obese Individuals With Moderate Or Severe Disease: Scale Sleep Apnoea Trial. (10th November 2014) - Collier, A; Blackman, A; Foster, G; Zammit, G; Rosenberg, R; Wadden, T; Aronne, L; Claudius, B; Jensen, T; Mignot, E
Abstract : Aims/objectives: This randomised, double-blind, parallel-group trial compared the effects of liraglutide 3.0 mg to placebo, both as adjunct to diet and exercise, on obstructive sleep apnoea (OSA) severity and body weight. Content: Obese individuals (n = 359) without diabetes who had moderate or severe OSA and were unwilling/unable to use continuous positive airway pressure therapy were randomised 1:1 to liraglutide 3.0 mg or placebo for 32 weeks (baseline characteristics: 48.5 years, males 71.9%, apnoea–hypopnoea index [AHI] 49.2 events/h, body weight 117.6 kg, BMI 39.1 kg/m 2, HbA1c 5.7%). Outcomes: At end-of-trial, the reduction in AHI was significantly greater with liraglutide 3.0 mg than placebo (Table ). Liraglutide 3.0 mg produced significantly greater weight loss compared with placebo (Table ) and enabled more individuals to reach ≥5% and >10% weight loss targets after 32 weeks (p < 0.0001, both). Oxygen saturation, polysomnographic measures, HbA1c and systolic blood pressure (SBP) at 32 weeks are summarised (Table ). Nausea and diarrhoea were the most common adverse events with liraglutide 3.0 mg (27% and 17% of individuals, respectively). Discussion: Liraglutide 3.0 mg produced significantly greater reductions than placebo in AHI, body weight, SBP and HbA1c in obese individuals with moderate/severe OSA and was generally well tolerated.